1997
DOI: 10.1111/j.1528-1157.1997.tb01237.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Subpial Transection for Control of Epileptic Seizures: Effectiveness and Safety

Abstract: Summary:Purpose: To assess the efficacy and safety of multiple subpial transection (MST), a new technique in epilepsy surgery, alone and in combination with resection.Methods: MST was performed in 22 patients with intractable epilepsy, 10 of whom were treated with a combination of a resection and MST in functionally important cortex, 6 of whom were treated with a combination of a resection and MST performed outside functionally important cortex, and 6 of whom were treated with MST alone.Results: Of the 6 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
2
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 28 publications
2
56
2
3
Order By: Relevance
“…Most previous reports found better results when resection was combined with MST than when MST was performed alone (4,5). We observed this discrepancy only for generalized seizures.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Most previous reports found better results when resection was combined with MST than when MST was performed alone (4,5). We observed this discrepancy only for generalized seizures.…”
Section: Discussioncontrasting
confidence: 68%
“…The approach was conceived and advocated for the specific situation in which resective surgery was precluded by the likelihood of neurologic compromise, and was later adapted for the treatment of some specific syndromes (2,3). Subsequently MST has been slowly (and somewhat randomly) adopted at many centers around the world, some of which have published experience with specific patient selection, seizure outcome, and neurologic status (4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple subpial transection (MST) is an increasingly popular surgical treatment for certain intractable forms of epilepsy (35)(36)(37)(38). The aim of MST is to sever critical sets of horizontal axons that mediate seizure spread, while sparing vertical columns of cortical neurons and connections that are thought to mediate the most essential aspects of neocortical function (39-42).…”
Section: Relevance For Multiple Subpial Transectionmentioning
confidence: 99%
“…Slight technical variations of MST have been published by Morrell et al (36), Kaufman et al (43), and Hufnagel et al (35), and the efficacy of MST has been demonstrated when used alone and in conjunction with resection (35)(36)(37). But the success of MST must be assessed by considering both seizure control and postoperative neurologic function.…”
Section: Relevance For Multiple Subpial Transectionmentioning
confidence: 99%